History of Establishment Procedures of PT Sinergi Express in Medan City - Syifa Amelia Rezeki; Rifat Hibrizi Al Banjari; Dimas Very Prabowo; Fahrezi Maulana (Formosa Journal of Science and Technology, 2023)
PT. Sinergi Ekspress Logistindo Pratama (SINEX Cargo) is a private company focused on shipping pharmaceutical goods, general cargo goods, city courier delivery. The company has been established since August 8, 2000, founded in Medan by Mr. Iskandar Zulkarnain, SE, AMP who has experience in the fields of Domestic, International Cargo and Courier Companies, the purpose of this research is to find out the History of Establishment and Procedures of Pt Sinergi Express. The research method used is Field Search research.